The late Middle Pleistocene Homo erectus of the Madura Strait, first hominin fossils from submerged Sundaland - H.W.K. Berghuis; Yousuke Kaifu; Unggul Prasetyo Wibowo; Thijs van Kolfschoten; Indra Sutisna; Sofwan Noerwidi; Shinatria Adhityatama; Gert van den Bergh; Eduard Pop; Rusyad Adi Suriyanto; A. Veldkamp; Josephine C.A. Joordens; et al. (Quaternary Environments and Humans)
Eastern Asia yielded a rich fossil record of Pleistocene hominins, ranging from Homo erectus and the diminutive island species Homo floresiensis and Homo luzonensis, to post-erectus grade late archaic Homo (including Denisovans), and finally to anatomically modern humans. The Sunda Shelf played an important role in the dispersal and evolution of hominin populations. The shelf has been widely exposed during most of the Pleistocene, forming a landmass known as Sundaland. Today, the area holds the world’s largest shelf sea. Thus far, hominin fossils from submerged Sundaland were not available. Here we report on the finding of two hominin cranial fragments from the submerged Sunda Shelf, retrieved during a dredging work in the Madura Strait, off the Java coast. The specimens derive from the sandy fill of a late Middle Pleistocene submerged valley of the Solo River and consist of a frontal fragment and a parietal fragment. Metric and morphological comparisons with Pleistocene skulls from the Asian mainland, Java and Flores point to a relation with the late Homo erectus of Java, in particular with the crania from Sambungmacan. The Madura Strait hominins were probably part of an MIS6 population that lived along the Solo, which in this period continued eastward over the exposed shelf area of the Madura Strait. Probably, the large perennial rivers of Sundaland offered good living conditions for Homo erectus, in a late Middle Pleistocene climate setting that was relatively dry.